METODE MEMAHAMI ISLAM - Wardah, Fatma; Nati, Rahmi; Meliati; Hikmah, Nurul (QATHRUNÂ, 2024)
Method is a scientific discipline that provides instruction about the methods and processes of scientific inquiry. Methods for understanding Islam must be seen from various points of view. For example, if we look at Islam from one point of view, we will only see one aspect of its long-term phenomenon. Even though we can see it correctly, it is not enough to understand Islam as a whole. Because Islam has many aspects and dimensions, each person can find the perspective that best suits his or her field. In other words, all Muslim intellectuals must use the scientific disciplines they have to understand Islamic teachings originating from the Koran and al-Sunnah. The method of understanding Islam is a term that refers to the way a person understands, knows and comprehends Islamic teachings. This article is a library research method, namely research whose object of study uses library data in the form of books, journals, articles as data sources. This research was carried out by reading, reviewing and analyzing various existing literature. By using this method, you can find out more deeply about the discussion of a topic.